OPEC's market power: An empirical dominant firm model for the oil market - Rolf Golombek; Alfonso A. Irarrazabal; Lin Ma (University of Oslo, Department of Economics, 2015)
We estimate a dominant firm-competitive fringe model for the crude oil market using quarterly data on oil prices for the 1986-2009 period. All estimated structural parameters have the expected sign and are significant. We find that OPEC exercised market power during the sample period. Counterfactual experiments indicate that world GDP is the main driver of long-run oil prices, however, supply (depletion) factors have become more important in recent years.
Keywords: L13; L22; Q31; 330; oil; dominant firm; market power; OPEC; Lerner index; oil demand elasticity; oil supply elasticity